Indexes of power and aerobic capacity obtained in cycle ergometry and treadmill running: comparisons between sedentary, runners, cyclists and triathletes - Caputo, Fabrizio [UNESP]; Stella, Sérgio Garcia; Mello, Marco Túlio de; Denadai, Benedito Sérgio [UNESP] (Sociedade Brasileira de Medicina do Exercício e do Esporte, 2003)
The objectives of this study were: a) to determine, in a cross-sectional manner, the effect of aerobic training on the peak oxygen uptake, the intensity at O2peak and the anaerobic threshold (AnT) during running and cycling; and b) to verify if the transference of the training effects are dependent on the analized type of exercise or physiological index. Eleven untrained males (UN), nine endurance cyclists (EC), seven endurance runners (ER), and nine triathletes (TR) were submitted, on separate days, to incremental tests until voluntary exhaustion on a mechanical braked cycle ergometer and on a treadmill. The values of O2peak (ml.kg-1.min-1) obtained in running and cycle ergometer (ER = 68.8 ± 6.3 and 62.0 ± 5.0; EC = 60.5 ± 8.0 and 67.6 ± 7.6; TR = 64.5 ± 4.8 and 61.0 ± 4.1; UN = 43.5 ± 7.0 and 36.7 ± 5.6; respectively) were higher in the group that presented specific training in the modality. The UN group presented the lower values of O2peak, regardless of the type of exercise. This same behavior was observed for the AnT (ml.kg-1.min-1) determined in running and cycle ergometer (ER = 56.8 ± 6.9 and 44.8 ± 5.7; EC = 51.2 ± 5.2 and 57.6 ± 7.1; TR = 56.5 ± 5.1 and 49.0 ± 4.8; UN = 33.2 ± 4.2 and 22.6 ± 3.7; respectively). It can be concluded that the transference of the training effects seems to be only partial, independently of the index (O2peak, IO2peak or AnT) or exercise type (running or cycling). In relation to the indices, the specificity of training seems to be less present in the O2peak than in the IO2peak and the AnT.
Keywords: Specificity; Maximal oxygen uptake; Anaerobic threshold; Running; Cycling